ECOEXPERIENCE LEARNING: LEARNING STRATEGY FOR CRITICAL ENVIRONMENTAL EDUCATION - Luciane Schulz (Universidade Federal de Sergipe, 2018)
The following article has the objective to diffuse Ecoexperience Learning as a Critical Environmental Education (CEE). Its learning proposal has been applied in an interventional research which constitutes in PhD thesis subsidies. This article arguments that Critical Environmental Education conceptions are able to be epistemologically enriched when intertwined along with: Affectivity which is a determinant of one´s relation with the world; Ecoexperinces being assumptions to attentive experiences within one´s environment; Emancipation which can set forth stimulating ways of learnings which will guide students in making decisions with critical sense. Results reveal that Ecoexperience Learning promoted the eco-training of students when dealing with such ecoexperience proposals which made this research a milestone in their life. An emerging battle cry in name of saving and preserving land for cultural purposes as well as for means of survival has at last been heard. It is concluded that the objectives were achieved since data source in its broad and varied presentations of expression validate Ecoexperience Learning as a Critical Environmental Education learning strategy.